Foreign Market Entry Modes Choice of Chinese Commercial Banks - Liu, Tiezheng (2011)
ABSTRACT The past decade has witnessed unprecedented booming in the commercial banks in China, which have not only withstood the financial crisis, but also came out with outstanding result in terms of international competitiveness. Under this backdrop, domestic commercial banks should take the action of internationalisation: to speed up the presence of the network and branches overseas, to improve their reputation and brand image globally, to expand the scope of products and to improve the ability of serving the high-end customers and transnational companies. This study attempts to expand what is known about the relationship between the general theories of FDI, especially the OLI paradigm of Dunning’s, and entry mode choice of Chinese banking firms. Based on the theory, the paper will analyse features and merits of Greenfield investment and M&A in banking transnational operation, as well as factors considered in making the choice. The findings of this study are not only for the explanation of ICBC but also for the strategy lessons it may offer to other Chinese banks. In brief, we set out to answer two main questions in the paper: what are the characteristics in the internationalisation process of the Chinese banks? What is the best entry mode for a Chinese bank to expand globally? Key words: OLI advantages; Internationalisation; Chinese Banks; Entry Mode; ICBC.